2018
DOI: 10.1111/jwas.12506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gonadal Development in Diploid and Triploid Hybrid Groupers, Epinephelus coioides♀ × Epinephelus lanceolatus

Abstract: In this study, the gonadal development of 10‐ to 43‐mo‐old diploid and triploid orange‐giant grouper hybrids, Epinephelus coioides♀ × Epinephelus lanceolatus♂, was investigated. The diploid hybrid groupers exhibited normal gonadal development and experienced vitellogenesis at 43 mo of age. In contrast, the triploid gonad was masculinized and gradually filled with spermatogenic cysts. Radioimmunoassays revealed that the diploid hybrids showed high serum E2 levels at 10 and 43 mo and high T levels at 43 mo, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The previous description of the karyotypes of E. coioides, which classified the Ag-NOR pair as submetacentric chromosomes (2sm+46a; Wang et al 2010), and E. lanceolatus (8sm+40a;Jiun & Mei 2009) were considered in the estimates of karyotypic divergences of the species involved in interspecific crossings. Hybrids of E. coioides ♀ (48a/2sm+46a; FN=48/50) X E. lanceolatus ♂ (2n=6sm+42a/8sm+40a; FN=54/56), with at least four detectable pericentric inversions (ΔFN=4-8), reach maturity and normal gonadal development (Li et al 2018). Hybrids from phylogenetically close lineages may even show a greater growth and adaptability than their parental species (Senoo 2006, Liufu et al 2007, Huang et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The previous description of the karyotypes of E. coioides, which classified the Ag-NOR pair as submetacentric chromosomes (2sm+46a; Wang et al 2010), and E. lanceolatus (8sm+40a;Jiun & Mei 2009) were considered in the estimates of karyotypic divergences of the species involved in interspecific crossings. Hybrids of E. coioides ♀ (48a/2sm+46a; FN=48/50) X E. lanceolatus ♂ (2n=6sm+42a/8sm+40a; FN=54/56), with at least four detectable pericentric inversions (ΔFN=4-8), reach maturity and normal gonadal development (Li et al 2018). Hybrids from phylogenetically close lineages may even show a greater growth and adaptability than their parental species (Senoo 2006, Liufu et al 2007, Huang et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al () also explored mechanisms of gonadal masculinization of triploid, but in hybrid groupers Epinephelus coioides ♀ × Epinephelus lanceolatus ♂. They found that the diploid hybrids showed high serum E2 levels at 10 and 43 mo and high T levels at 43 mo, while the triploid hybrids showed high E2 levels at 18 and 30 mo and high T levels at 18 mo.…”
Section: Special Issue Summarymentioning
confidence: 99%